A combined experimental and simulation method for appraising the energy performance of green roofs in Ningbo's Chinese climate - Kokogiannakis, Georgios; Darkwa, Jo; Yuan, Kate (Springer, 2014)
A passive means of lowering the energy demand of buildings is the application of green roofs. The complexity between heat and moisture exchanges in green roof layers and the large variations of green roof types make the need for experimental or simulation assessments necessary for quantifying the energy benefits from green roofs. The current treatment of green roofs in simulation programs is either over-simplistic, for example by ignoring heat and moisture exchanges such as evapotranspiration, or the more advanced models have limitations and require inputs that are rarely available in practice. In this paper a combination of experimental and modelling techniques are used to assess the potential heating and cooling load reductions from the application of green roofs in the subtropical climate of Ningbo in China. The method provides a generalised energy performance assessment of green roofs in Ningbo by overcoming the limitations of existing gree